INTERACTION FACTORS OF UKRAINE IN THE AREA OF INTER-STATE FINANCIAL COOPERATION - Ustynova, Iryna; Uryadko, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: study of legal aspects of public financial activity in Ukraine by international financial organizations, analysis of their legal status, as well as their impact on the revenues of the general fund of the State Budget of Ukraine. Methods: general scientific and special legal methods were used in the work. Results: it was concluded that Ukraine’s cooperation with international financial organizations contributes to the improvement of the economic situation in the country and opens opportunities for attracting international financial resources aimed at implementing priority projects for the development of our country. Discussion: searching for ways to overcome existing problems in Ukraine’s cooperation with international financial organizations.